Smart technology and the emergence of algorithmic bureaucracy: Artificial intelligence in UK local authorities - Vogl, Thomas M. et al (Public Administration Review)
In recent years, local authorities in the UK have begun to adopt a variety of (3z(Bsmart(3y (Btechnological changes to enhance service delivery. These changes are having profound impacts on the structure of public administration. Focusing on the particular case of artificial intelligence, specifically autonomous agents and predictive analytics, a combination of desk research, a survey questionnaire, and interviews were used to better understand the extent and nature of these changes in local government. Findings suggest that local authorities are beginning to adopt smart technologies and that these technologies are having an unanticipated impact on how public administrators and computational algorithms become imbricated in the delivery of public services. This imbrication is described as algorithmic bureaucracy, and it provides a framework within which to explore how these technologies transform both the socio-technical relationship between workers and their tools, as well as the ways that work is organized in the public sector.- Reproduced s
Keywords: Smart technology, Algorithmic, Bureaucracy, Artificial intelligence, Local authorities